2021
DOI: 10.1371/journal.pone.0248624
|View full text |Cite
|
Sign up to set email alerts
|

Allergic rhinitis is associated with atmospheric SO2: Follow-up study of children from elementary schools in Ulsan, Korea

Abstract: Objectives The purpose of this study was to examine the association of allergic rhinitis with air pollutant concentrations using the follow-up data of elementary school children in Ulsan, Korea. Methods All students of four elementary schools in Ulsan, South Korea were surveyed at two-year intervals. The survey used data collected five times, over a nine-year period from June 2009 to April 2018. The questionnaire used in the survey was a modified version of the ISAAC (International society of asthma and alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 69 publications
(81 reference statements)
0
11
0
Order By: Relevance
“…20 Conversely, other studies showed the results that PM 10 was not associated with the AR prevalence 15 or even reported that increased PM 10 was associated with a reduced risk of AR prevalence. 16 However, the study populations in these studies were limited to participants living in a designated metropolitan city. These diversities in the scale of the study population might have led to the discrepancies in the results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Conversely, other studies showed the results that PM 10 was not associated with the AR prevalence 15 or even reported that increased PM 10 was associated with a reduced risk of AR prevalence. 16 However, the study populations in these studies were limited to participants living in a designated metropolitan city. These diversities in the scale of the study population might have led to the discrepancies in the results.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] However, previous studies concerning air pollutants and inflammatory sinonasal diseases have been limited to analyzing subgroups of regional populations, and the results were inconsistent. 2,9,15,16 Because there is such a debate in this subject, in this population-based cross-sectional study we aimed to verify the association between the concentration of air pollutants and the prevalence of inflammatory sinonasal diseases such as allergic rhinitis (AR) and chronic rhinosinusitis (CRS), using the data of South Koreans on a nationwide scale. Additionally, we investigated whether immunoglobulin E (IgE) levels or rhinitis-related endoscopic findings of the nasal cavity were related to each air pollutant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 There was a strong correlation between PM 10 , SO 2 , NO 2 , and AR in Zhang's study 25 . A study in Korea demonstrated that AR and SO 2 were associated with high risk, and PM 10 was associated with low risk 27 (Kim, 2021). There was a study that researched significant.…”
Section: Discussionmentioning
confidence: 99%
“…The values for estimating air pollution concentrations were based on the levels produced by Kim et al (2021)’s study [ 42 ]. Air pollution estimates were based on the monthly average data from 13 air quality monitoring sites (AQMS) under the National Institute of Environmental Research (NIER).…”
Section: Methodsmentioning
confidence: 99%